Design, Fabrication, and Experimental Evaluation of a 435 MHz Helical Antenna for 433 MHz IoT Modules - Rusfa Rusfa; Rozeff Pramana; Bavitra Bavitra; Ferly Oktavia; M. Hasbi Sidqi Alajuri; Andreas M Simannulang (National Research and Innovation Agency, 2025)
The rapid growth of wireless communication demands within Internet of Things (IoT) applications requires antennas that exhibit high efficiency, compact dimensions, and reliable performance in the UHF band. This study aims to design, simulate, fabricate, and evaluate the performance of a helical antenna operating at 435 MHz, with its results compared against a slot antenna. The design process was conducted using CST Studio Suite with parameter optimization to achieve an optimal configuration. The prototype was fabricated using copper wire as the radiating element and an aluminum ground plane. Experimental testing was carried out with a UHF Antenna Demonstrator, followed by validation through a 433 MHz RF module integrated with Arduino. The simulation results indicated that the optimized helical antenna achieved aVoltage Standing Wave Ratio (VSWR) of 1.8 and a gain of 11.5 dBi. In contrast, the measurement results demonstrated improved performance, with a VSWR of 1.05, a return loss of −32.4 dB, and a bandwidth of 41 MHz. Comparative analysis revealed that the helical antenna outperformed the slot antenna in terms of efficiency, directional radiation pattern, and transmission distance, reaching up to 25 m compared to 15 m for the slot antenna. These findings confirm that the helical antenna is a more suitable and effective solution for UHF IoT communication systems, providing reliable performance for modern wireless applications.